Review Of The Implementation Of The Break Event Point Theory In Traditional Markets - Afifatul Fitriyah; Imam Sopingi; Kusnul Yuni (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2026)
This study aims to analyze the implementation of the break-even point (BEP) theory in the Cukir traditional market, Jombang, to help small traders manage their businesses efficiently and determine the minimum sales level to reach the break-even point. The research focuses on identifying fixed costs, variable costs, and external factors such as consumer purchasing power that influence the achievement of BEP. The research method uses a quantitative descriptive approach with primary data from interviews and questionnaires, as well as secondary data in the form of simple financial records. The BEP calculation is carried out by dividing the total fixed costs by the contribution margin per unit, while the validity of the data is tested through triangulation from various sources. The results show that the implementation of BEP helps traders understand the minimum sales requirements and improves their financial literacy. For example, a grocery trader needs to sell a minimum of 250 kilograms of rice per month to reach the break-even point. The implementation of BEP also encourages more structured financial records and more effective sales strategies, supporting the sustainability of micro-enterprises in the traditional market.